A molten-salt protected pyrolysis approach for fabricating a ternary nickel–cobalt–iron oxide nanomesh catalyst with promoted oxygen-evolving performance. Issue 33 (24th March 2020) - Xie, Junfeng; Guo, Yanqing; Lou, Shanshan; Wei, Zimeng; Hao, Pin; Lei, Fengcai; Tang, Bo
Abstract : A NiCoFe oxide nanomesh with two-dimensional morphology, quasi-single-crystalline feature and remarkable OER performance was fabricated via a molten-salt protected pyrolysis approach. Abstract : In this work, a highly porous ternary NiCoFe oxide nanomesh with two-dimensional morphology and quasi-single-crystalline (QSC) feature was synthesized via a convenient molten-salt protected pyrolysis approach, which achieves remarkable OER performance with a low overpotential, high current density, improved intrinsic activity and superior operational stability.